Plastid Envelope-Localized Proteins Exhibit a Stochastic Spatiotemporal Relationship to Stromules - Delfosse, Kathleen; Wozny, Michael R.; Barton, Kiah A.; Mathur, Neeta; Griffiths, Nigel; Mathur, Jaideep (Frontiers in Plant Science, 2018)
Plastids in the viridiplantae sporadically form thin tubules called stromules that increase the interactive surface between the plastid and the surrounding cytoplasm. Several recent publications that report observations of certain proteins localizing to the extensions have then used the observations to suggest stromule-specific functions. The mechanisms by which specific localizations on these transient and sporadically formed extensions might occur remain unclear. Previous studies have yet to address the spatiotemporal relationship between a particular protein localization pattern and its distribution on an extended stromules and / or the plastid body. Here, we have used discrete protein patches found in several transgenic plants as fiducial markers to investigate this relationship. While we consider the inner plastid envelope-membrane localized protein patches of the GLUCOSE 6-PHOSPHATE / PHOSPHATE TRANSLOCATOR1 and the TRIOSE-PHOSPHATE/ PHOSPHATE TRANSLOCATOR 1 as artefacts of fluorescent fusion protein over-expression, stromule formation is not compromised in the respective stable transgenic lines that maintain normal growth and development. Our analysis of chloroplasts in the transgenic lines in the Arabidopsis Columbia background, and in the arc6 mutant, under stromule-inducing conditions shows that the possibility of finding a particular protein-enriched domain on an extended stromule or on a region of the main plastid body is stochastic. Our observations provide insights on the behaviour of chloroplasts, the relationship between stromules and the plastid-body and strongly challenge claims of stromule-specific functions based solely upon protein localization to plastid extensions.